From Thomas Bernhard to Alberto Montero's Los incapaces: one's own traumas and others' writings (El Hilo de la Fabula, 2024)
Los incapaces (2015) is so far the only published novel by the Argentinean writer Alberto Montero. In it, the psychoanalyst Monroe recounts his misadventures, which extend, through a single sentence without full stops, for almost four hundred pages. To consolidate his voice, Monroe resorts to what he calls his «maneras bernhardianas»: he recognizes Thomas Bernhard as his undisputed master and uses the textuality of pastiche, in which the style of another author is copied and, in some cases, exaggerated. Beyond the humorous effects achieved by the voice of the Bernhardian narrator refracted through Monroe, this borrowing achieves a liberation of writing that finally circumvents the vicissitudes of interruption. Monroe, who has left all his literary projects unfinished, cannot stop writing, and this produces a dissociation between the subject and writing, which we propose to call emancipated or alienated writing. The aim of this paper is to examine the theory of writing outlined in Los incapaces—whose roots are undoubtedly in Bernhard's texts—a theory that also investigates the relationships of readings and rewritings between Argentinean and European literature.
Keywords: style; emancipated writing; interrupted writing; Thomas Bernhard; Alberto Montero